DEVELOPING A SUSTAINABLE URBAN TOURISM - Andari, Rini (Universitas Pendidikan Indonesia, 2019)
This paper aims to explain the importance of creating sustainable urban tourism. The method used is library research. Tourism is a useful activity that can preserve cultural and historical heritage and can prosper society. Throughout history, the city has become the focus of tourism activities, providing accommodation, entertainment and other facilities for tourists. Achieving sustainable urban development requires the preservation of historical sites and cultural structures. By preserving a cultural heritage, and reviving it in a new way, is one form of realization of effective sustainable development.